Antipsychotic Dose in Acute Schizophrenia: A Meta-analysis. (16th May 2020) - Takeuchi, Hiroyoshi; MacKenzie, Nicole E; Samaroo, Dominic; Agid, Ofer; Remington, Gary; Leucht, Stefan
Abstract: Little is known regarding optimal antipsychotic doses in the acute phase of schizophrenia. The aim of the present study was to employ the concept of minimum effective dose (MED) in examining efficacy and tolerability within this population. MED was identified for each antipsychotic through a previous systematic review. We then identified double-blind placebo-controlled randomized trials that involved fixed-dose antipsychotic monotherapy in acute schizophrenia and compared the identified MED vs higher doses of the same oral antipsychotic. Studies were selected from a recent meta-analysis examining dose–response relationship of second-generation antipsychotics and haloperidol. We extracted the data on study discontinuation, psychopathology, extrapyramidal symptoms, and treatment-emergent adverse events. For each antipsychotic, we conducted a meta-analysis to compare outcomes between MED and 2-fold MED, and MED and 3-fold MED. A total of 26 studies involving 5618 patients were included in the meta-analysis. In terms of study discontinuation, significant differences were found in study discontinuation due to lack of efficacy between MED and higher doses, in favor of 2-fold and 3-fold MEDs. Regarding psychopathology, both 2-fold and 3-fold MEDs were superior to MED for total and positive symptom scores. As for side effects, 2-fold MED proved inferior to MED for parkinsonism scores and diarrhea, whereas 3-fold MED was inferior for akathisia, somnolence, and vomiting. Findings suggest that clinicians can dose an antipsychotic at 2-fold or 3-fold MED for patients with acute schizophrenia but should closely monitor side effects.